Tracking animal migration with stable isotopes - Hobson, Keith Alan, 1954-; Wassenaar, Leonard I. (Terrestrial ecology series, 2008)
Many questions in animal biology require the ability to track animal movement by using multi-disciplinary and technological innovations. Over the past decade, intrinsic chemical markers have become especially key in the study of migration. Stable isotopes are a successful example of instrinic markers that have yielded new and valuable insights into animal migration. This book provides a consolidated overview of the current knowlesge of stable isotopes in terrestrial migration research questions, and to provide a practical handbook for those considering using stable isotopes in their migration research. * Presents information for readers to understand how to apply isotopic methods for tracking * Critical information on areas for future research * Practical guidelines and discussions of sample collection, sample preparation, isotope-ratio mass spectrometry data analysis, and issues of isotopic exchange and heterogeneity * Enhanced understanding of data and statistical analysis in isotope-based studies of migratory animals.